Antonio López de Mirafuentes y Ortiz de Bobadilla, caballero de la Orden de Santiago - Pastor Abáigar, Víctor (Huarte de San Juan. Geografía e Historia, 2015)
Through this work we want to present a member of 17th century rural nobility. His father’s family had, in previous generations since the Middle Ages, occupied regimentary positions in Los Arcos, and his mother’s family were part of a distinguished social status in the town of Azagra in the south of Navarre. He was the only child of his father’s first marriage and as an adult he inherited a house, land, livestock and bodegas, all with entailed estate. His father’s good management of the inheritance is clear. Of particular note are the private chapel in the parish cloisters of Los Arcos and an oratory in his ancestral house. During his military training in the Order of Saint James, he served under Luis Méndez de Haro y Guzmán, the third Count-Duke de Olivares.
Keywords: López Feo de Mirafuentes; etnography; master builders; making and selling wine; Knight of Santiago in Convent of Capuchinos